Temporal variability in total, micro- and nano-phytoplankton primary production at a coastal site in the Western English Channel. (September 2015) - Barnes, Morvan K.; Tilstone, Gavin H.; Suggett, David J.; Widdicombe, Claire E.; Bruun, John; Martinez-Vicente, Victor; Smyth, Timothy J.
Highlights: Absorption coefficients were used to calculate coastal primary production (PP). Variability in PP at weekly scales was related to changes in phytoplankton species. A decline in nano-phytoplankton PP and decrease in winter nitrate were coupled. Micro-phytoplankton PP was enhanced in summer during high precipitation. This may have a positive feedback on climate change through increased CO2 drawdown. Abstract: Primary productivity and subsequent carbon cycling in the coastal zone have a significant impact on the global carbon budget. It is currently unclear how anthropogenic activity could alter these budgets but long term coastal time series of hydrological, biogeochemical and biological measurements represent a key means to better understand past drivers, and hence to predicting future seasonal and inter-annual variability in carbon fixation in coastal ecosystems. An 8-year time series of primary production from 2003 to 2010, estimated using a recently developed absorption-based algorithm, was used to determine the nature and extent of change in primary production at a coastal station (L4) in the Western English Channel (WEC). Analysis of the seasonal and inter-annual variability in production demonstrated that on average, nano- and pico-phytoplankton account for 48% of the total carbon fixation and micro-phytoplankton for 52%. A recent decline in the primary production of nano- and pico-phytoplankton from 2005 to 2010 was observed, corresponding with a decrease in winter nutrient concentrations and a decrease in the biomass of Phaeocystis sp. Micro-phytoplankton primary production (PPM ) remained relatively constant over the time series and was enhanced in summer during periods of high precipitation. Increases in sea surface temperature, and decreases in wind speeds and salinity were associated with later spring maxima in PPM . Together these trends indicate that predicted increases in temperature and decrease in wind speeds in future would drive later spring production whilst predicted increases in precipitation would also continue these blooms throughout the summer at this site.